The Influence of Market Orientation, Product Innovation, Digital Marketing, and Brand Equity on Business Performance in Creative Startups - Sutiksno, Dian Utami; Tanihatu, Maudy Marla; Tjokro, Cynthia Imelda; Nahuway, Victorio Fernando (Eastasouth Institute, 2025)
This study investigates the influence of market orientation, product innovation, digital marketing, and brand equity on business performance in creative startups in Indonesia. Utilizing a quantitative research approach, data were collected from 250 founders and managers of startups across various creative sectors. Respondents completed a structured questionnaire using a 5-point Likert scale. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3.0). The results reveal that all four variables—market orientation, product innovation, digital marketing, and brand equity—have a significant and positive effect on business performance. Among them, brand equity emerged as the strongest predictor. The model explained 67.1% of the variance in business performance, with all constructs demonstrating good reliability, validity, and predictive relevance. These findings underscore the strategic importance of customer orientation, innovation, digital engagement, and brand strength in enhancing startup performance in Indonesia’s growing creative economy.